Antioxidant study of pulps and peels of dragon fruits: a comparative study - Ruzlan, Nurliyana; Syed Osman Idid, Syed Zahir Idid; Koya, Mustapha Suleiman; Mohamed Rehan, Aisyah; Kamarudin, Kamarul Rahim (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The aim of this study is to compare antioxidant level and activities (i.e. primary and secondary) in pulps and peels of two species of dragon fruits, Hylocereus undatus (white dragon fruit) and Hylocereus polyrhizus (red dragon fruit). Total phenolic content (TPC) assay demonstrated that peels of both Hylocereus species contained higher phenolic content than the pulps. The phenolic content in peels of H. undatus was higher than H. polyrhizus, but the phenolic content in pulps of H. undatus was much lower than H. polyrhizus. 2, 2, diphenyl-1-picrylhydrazyl (DPPH) assay showed that radical scavenging activities of peels for both species were higher than the pulps. For ferrous ion chelating (FIC) assay, peels and pulps of both Hylocereus species showed moderate metal ion chelating effect as compared to EDTA. Overall, the results suggested that the TPC showed good relationship with the primary antioxidant activities for general comparison between the peels and the pulps.